Penggunaan Media Pembelajaran Power Point terhadap Keaktifan Belajar Siswa - Anita Amelia Ole; Yulianti Laoh; Elizabeth, M.M. Lasut (Departement of Mathematics Education, 2023)
Power-point learning is learning that uses slides by displaying images, videos, photos, and animations in delivering material to make it more interesting to increase student learning activity. This research aims to see the level of use of PowerPoint learning media and students' active learning. The results of this research show that there is a significant relationship between the use of PowerPoint learning media and students' active learning with the mean (Sig = .000 ≥ α = 0.05). This research is quantitative descriptive correlative, mean score, and Spearman test. Then the sampling technique used the convenience sampling method. The instrument used was a questionnaire adapted from Rudi (2014) and Suardi (2019). The population of this study was 127 students from Advent Unklab Middle School class VIII who were registered in the 2021-2022 academic year. The results of this research found that the level of use of PowerPoint learning media and students' active learning were in the high category.